2016
DOI: 10.1016/j.physio.2015.03.3721
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain characteristics associated with lower balance confidence in community-dwelling older adults

Abstract: Please cite this article as: Stubbs B, Schofield P, Patchay S, Leveille S, Musculoskeletal pain characteristics associated with lower balance confidence in community-dwelling older adults, Physiotherapy (2015), http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
(53 reference statements)
0
20
1
Order By: Relevance
“…[28] Deficiencies or suboptimal performance in each of these important factors are established risk factors for falls [29] and improvements in each of these may account for a reduction in falls. Such improvements may also improve balance confidence in older adults [30], which may therefore account for the improvements in fear of falling reported in the included studies.…”
Section: Discussionmentioning
confidence: 91%
“…[28] Deficiencies or suboptimal performance in each of these important factors are established risk factors for falls [29] and improvements in each of these may account for a reduction in falls. Such improvements may also improve balance confidence in older adults [30], which may therefore account for the improvements in fear of falling reported in the included studies.…”
Section: Discussionmentioning
confidence: 91%
“…2). One recent study discussed this hypothesis 43) by explaining the previous findings that older people with a decline in physical performance were likely to have lower functional mobility with an increased risk of falls, and therefore, tended to avoid activities due to a fear of falling 44,45) . Another study also indicates that community-dwelling older people with…”
Section: Conflict Of Interestsmentioning
confidence: 99%
“…The Australian Institute of Health and Welfare reported that chronic back problems affect 27% of people aged between 65 and 74 years in Australia [9]. Furthermore, the severity and number of chronic musculoskeletal pain sites are associated with reduced balance performance and falls risk [10].…”
Section: Introductionmentioning
confidence: 99%